Numerical optimization of plasmid DNA delivery combined with hyaluronidase injection for electroporation protocol. (April 2020) - Peri, Daniele; Deville, Manon; Poignard, Clair; Signori, Emanuela; Natalini, Roberto
Highlights: Advanced Numerical Optimization Algorithm for Complex Experimental Protocols of DNA Delivery. Realistic Optimal Protocol Obtained by Computational Study. Possible Increase of 30% of DNA Delivery thanks to the Computational Optimization. Abstract: Background and Objective: The paper focuses on the numerical strategies to optimize a plasmid DNA delivery protocol, which combines hyaluronidase and electroporation. Methods: A well-defined continuum mechanics model of muscle porosity and advanced numerical optimization strategies have been used, to propose a substantial improvement of a pre-existing experimental protocol of DNA transfer in mice. Our work suggests that a computational model might help in the definition of innovative therapeutic procedures, thanks to the fine tuning of all the involved experimental steps. This approach is particularly interesting in optimizing complex and costly protocols, to make in vivo DNA therapeutic protocols more effective. Results: Our preliminary work suggests that computational model might help in the definition of innovative therapeutic protocol, thanks to the fine tuning of all the involved operations. Conclusions: This approach is particularly interesting in optimizing complex and costly protocols for which the number of degrees of freedom prevents a experimental test of the possible configuration.